2015
DOI: 10.1002/smll.201500627
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Epitaxial Core–Shell Nanocrystals with Tunable Magnetic Anisotropy

Abstract: Epitaxial core-shell CoO-CoFe2 O4 nanocrystals are fabricated by using pulsed laser deposition with the aid of melted material (Bi2 O3 ) addition and suitable lattice mismatch provided by substrates (SrTiO3 ). Well aligned orientations among nanocrystals and reversible core-shell sequence reveal tunable magnetic anisotropy. The interfacial coupling between core and shell further engineers the nanocrystal functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…From a numerical perspective when the NiO crystal grows in partial oxygen pressure, gas adsorption contributes to the decrease Δγ gas of the surface energy in eqs and . A few attempts have already been made, , but the practical difficulties of the measurement of gas adsorption are a significant and challenging problem. The incorporation of the effect of oxygen adsorption on the equilibrium shape analysis of epitaxial nanocrystals in the GWK framework forms a part of our future work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a numerical perspective when the NiO crystal grows in partial oxygen pressure, gas adsorption contributes to the decrease Δγ gas of the surface energy in eqs and . A few attempts have already been made, , but the practical difficulties of the measurement of gas adsorption are a significant and challenging problem. The incorporation of the effect of oxygen adsorption on the equilibrium shape analysis of epitaxial nanocrystals in the GWK framework forms a part of our future work.…”
Section: Discussionmentioning
confidence: 99%
“…This interface-controlled morphology is a ubiquitous phenomenon irrespective of the type (vapor/liquid/solid or chemical/physical) of phase deposition. , It is primarily governed by the preferred crystallographic orientation relationship and interface structure between the overlayer and the substrate . Furthermore, more complex factors such as gas absorption or chemisorption at the exposed facets or surface reconstruction during growth also play key roles. , As such, the ultimate functional performance is shown to be strongly dependent on such shape and surface termination-driven changes to the nanocrystals. , Therefore, the interpretation of why the nanocrystal adopts a certain shape and more importantly the prediction of morphology has thus evolved to be one of the most intensely studied topics in the design and development of free-standing epitaxial nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Liao et al demonstrated a mesocrystal system consisting of core-shell oxide nanocrystals, enabling researchers to create alternative ways to design magnetic systems. [86] In the study, the self-assembled antiferromagneticferrimagnetic CoO-Co x Fe 3−x O 4 nanocrystals were used as building blocks to form one more branch of mesocrystals, a discrete core-shell mesocrystal. [86] The discrete core-shell nanocrystals were epitaxially grown on substrates, where the epitaxy sets the orientations of building nanocrystal blocks, resulting in a two-dimensional magnetic mesocrystal.…”
Section: Perspectives Of Mesocrystal-embedded Oxide Systemsmentioning
confidence: 99%
“…[86] In the study, the self-assembled antiferromagneticferrimagnetic CoO-Co x Fe 3−x O 4 nanocrystals were used as building blocks to form one more branch of mesocrystals, a discrete core-shell mesocrystal. [86] The discrete core-shell nanocrystals were epitaxially grown on substrates, where the epitaxy sets the orientations of building nanocrystal blocks, resulting in a two-dimensional magnetic mesocrystal. Due to the epitaxy between selected materials and substrates, the OOP orientation, core-shell ratio, and core-shell sequence become key parameters to control the interfacial coupling to deliver desirable properties.…”
Section: Perspectives Of Mesocrystal-embedded Oxide Systemsmentioning
confidence: 99%